A Nation of Realtors® : A Cultural History of the Twentieth-Century American Middle Class - Hornstein, Jeffrey M., 1967- (Book collections on Project MUSE., 2005)
A history of the real estate profession that rethinks the impact of gender and class tensions in twentieth-century America.